Ant Species in Tropical Australian Tree Crops and Native Ecosystems-Is There a Mosaic? - Majer, Jonathan; Camer-Pesci, P. (1991)
Dominant arboreal ants are distributed in a mosaic-like fashion within tree-crop plantations throughout the New World and Old World tropics. This paper reports on the distribution of arboreal ants within mango plantations, rain forests, and woodlands in the tropical northern part of Australia. Only two genera of arboreal ants, Oecophylla and to a lesser extent Crematogaster, reach high densities on trees in the areas studied. Both genera tend to occupy large blocks of canopy, but in the spaces between their colonies the canopy is either devoid of ants, occupied by arboreal-nesting species of low colony size, or visited by ground-nesting species. The latter do not monopolise large, contiguous blocks of canopy. The result is a partial ant mosaic of Oecophylla and Crematogaster territories with few, or no, ants on the surrounding canopy. The situation in tropical Australia is compared with published records from elsewhere in the world, and the reasons for the differences which exist are discussed. Finally, the implications for pest management in Australian tropical tree crops are speculated upon.